Political Science in Asia and the Pacific Status Reports on Teaching and Research in Ten Countries. Social and Human Sciences in Asia and the Pacific, RUSHSAP Series on Occasional Monographs and Papers, 10 - Uchida, Takeo; United Nations Educational, Scientific, and Cultural Organization, Bangkok (Thailand). Regional Office for Education in Asia and Oceania ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
This publication contains reports on the status of teaching and research in political science in ten countries in the Asia-Pacific Region. These reports prepared according to a common guideline provide an opportunity for comparison. The essays review how political science has grown and taken root in the respective countries; the problems it faces; and future directions. Following an introduction, "Issues and Perspectives in Political Science in Asia and the Pacific," the country status reports for Japan, Republic of Korea, Thailand, Indonesia, Philippines, Malaysia, India, Bangladesh, Australia, and New Zealand are presented. (KWL)
Availability: United Nations Educational, Scientific, and Cultural Organization, Regional Office for Education in Asia and the Pacific, P.O. Box 1425, General Post Office, Bangkok 10500, Thailand.
Researchers.
Microfiche.
Keywords: Global Approach; Higher Education; International Education; Political Science; Regional Cooperation; Research; Research Reports; Social Science Research; Social Sciences; Reports, Descriptive